The dog and pony show : dog gets a pet - Mack, Jeff (Simon Spotlight, an imprint of Simon & Schuster Children's Publishing Division, 2024)
Pony has a surprise for Dog--a pet rock! Dog would have preferred a T-Rex, or a moose, or a cow for a pet, but Pony says if Dog gives the pet rock a name, Dog will like it more. Dog names his pet rock Lulu the T-Rex and says it likes to eat ponies! Uh-oh. Will Dog and Pony and Lulu learn to get along?